Hybrid Work Systems, Work Flexibility On Employees' Work-Life Balance Mediated By Organizational Support In Research And Innovation Agencies - Fajar Revy; Suharto; Muhammad Hari (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
To find out the existence of a hybrid work system, work flexibility on employees' work-life balance mediated by organizational support in research and innovation institutions. This study was conducted during the period 2025, with a focus on data and information collected over a period of 3-6 months. To get a comprehensive understanding about the implementation of the work hybrid system at brin impact from the implementation of efficiency programs budget. The results are in the form of a summarized main thing findings that is obtained based on the results of data analysis and discussion that has been described in the previous chapters. Compilation conclusion referring to the research goal and formulation of the problem set, so able to give the whole picture about the answer to the research problem.